HIGH-PRESSURE BEHAVIOUR OF SERPENTINE MINERALS: A RAMAN SPECTROSCOPIC STUDY - Auzende A.L.; Daniel I.; Reynard B.; Lemaire C.; Guyot F. (My University, 2004)
Four main serpentine varieties can be distinguished on the basis of their microstructures, i.e. lizardite, antigorite, chrysotile and polygonal serpentine. Among these, antigorite is the variety stable under high pressure. In order to understand the structural response of these varieties to pressure, we studied well-characterized serpentine samples by in situ Raman spectroscopy up to 10 GPa, in a diamond-anvil cell. All serpentine varieties can be metastably compressed up to 10 GPa at room temperature without the occurrence of phase transition or amorphization. All spectroscopic pressure-induced changes are fully reversible upon decompression. The vibrational frequencies of antigorite have a slightly larger pressure dependence than those of the other varieties. The O-H-stretching modes of the four varieties have a positive pressure dependence, which indicates that there is no enhancement of hydrogen bonding in serpentine minerals at high pressure. Serpentine minerals display two types of hydroxyl groups in the structure: inner OH groups lie at the centre of each six-fold ring while outer OH groups are considered to link the octahedral sheet of a given 1:1 layer to the tetrahedral sheet of the adjacent 1:1 layer. On the basis of the contrasting behaviour of the Raman bands as a function of pressure, we propose a new assignment of the OH-stretching bands. The strongly pressure-dependent modes are assigned to the vibrations of the outer hydroxyl groups, the less pressure-sensitive peaks to the inner ones.
Keywords: RAMAN SPECTROSCOPY; HIGH PRESSURE; SERPENTINE MINERALS; DIAMOND-ANVIL CELL